Social jetlag elicits fatty liver via perturbed circulating prolactin rhythm-mediated circadian remodeling of hepatic lipid metabolism - Peng-Zi Zhang; Ying-Huan Shi; Yu-Xin Guo; Ya-Yuan Li; Hong-Li Yin; Tian-Yu Wu; Ye Zhu; Jia-Xuan Jiang; Yan Bi (Military Medical Research)
Abstract Background The prevalence of circadian misalignment, particularly social jetlag (SJL), contributes significantly to the epidemic of metabolic disorders. However, the precise impact of SJL on the liver has remained poorly elucidated. Methods The rhythmicity of circulating prolactin (PRL) was evaluated in subjects with SJL and mice under SJL. The causative mechanism of SJL on fatty liver was explored using jetlag model in wild-type and Prl −/− mice. Luciferase reporter assay, electrophoretic mobility shift assay, and chromatin immunoprecipitation analysis were used to study the transcriptional mechanism of retinoic acid receptor-related orphan receptor α on PRL. RNA-seq on human and mice liver as well as circadian analysis were used to study the mechanism of SJL-associated desynchronized PRL on hepatic lipid metabolism. The therapeutic effect of PRL intervention on SJL-induced mice at different time points was compared. Results SJL increases the risk of metabolic dysfunction-associated steatotic liver disease (MASLD), mediated by the disruption of the rhythmicity of serum PRL. In particular, SJL inhibits the rhythmic transcription of PRL in the pituitary, leading to desynchronized PRL levels in circulation. Under jetlag conditions, the rhythmicity of the hepatic PRL signaling pathway was significantly dampened, which resulted in increased lipogenesis via inhibited hepatic mitogen-activated protein kinase/cyclin D1 expressions. Notably, PRL treatment at PRL nadir in jetlagged mice decreased hepatic lipid content and liver injury markers to a greater extent compared with conventional PRL administration. Conclusions Reprogrammed hepatic PRL signaling pathway with concomitant dysregulated lipid metabolism homeostasis was the causative mechanism of fatty liver under SJL, which was mediated through derailed serum PRL rhythm. Restoration of PRL rhythm could effectively alleviate SJL-induced fatty liver, providing new insight into treating MASLD.